REKONSTRUKSI IZIN PINJAM PAKAI KAWASAN HUTAN UNTUK KEGIATAN PERTAMBANGAN DI INDONESIA - Gunardi Gunardi; Ahmad Redi; Luthfi Marfungah (Faculty of Law - Tarumanagara University, 2021)
The potential wealth of mineral and coal resources in Indonesia provides room for conflicts of interest. Alignment in the overall implementation of regulations should minimize conflicts of interest. In 1989-2019 there were 457 conflicts of interest between forestry and mining in Indonesia. This research is intended to provide information on violations due to borrowing and using forest areas for mining in Indonesia. This study uses a juridical normative method. The final results of this study conclude that there is a need for firm legal materials and laws for resolving mining and forestry conflicts in Indonesia by using a licensing system. So that in terms of conflict resolution between mining and forestry jurisdictions, it does not delegate too much technical regulatory authority in its resolution. This research further examines the impact of conflicts between mining law areas and forest areas in Indonesia.